Asuhan Akupunktur pada kasus dengan Fluor Albus di Griya Sehat "de_maemun" Kabupaten Cirebon - Ade Siti Maemunah; Mayang Wulandari; Leny Candra Kurniawan; Chantika Mahadini; Rachmat Roebidin (Malahayati Nursing Journal, 2026)
ABSTRACT Fluor albus (pathological leukorrhea) remains a prevalent gynecological complaint in Indonesia, with conventional antimicrobial therapy often limited by side effects and drug resistance. This single-case study evaluated the clinical efficacy of acupuncture in managing fluor albus due to Spleen Qi Deficiency with Dampness Accumulation pattern according to Traditional Chinese Medicine (TCM) principles. A 43-year-old female participant presenting with excessive white-yellowish sticky vaginal discharge, fatigue, abdominal distension postprandially, unformed stools, and cold-heavy sensation in extremities received six acupuncture sessions twice weekly at Griya Sehat "de_maemun", Cirebon. The intervention protocol included tonification techniques at SP-6 (Sanyinjiao), SP-4 (Gongsun), ST-36 (Zusanli), CV-6 (Qihai), GB-26 (Daimai), and BL-20 (Pishu), combined with reduction techniques at SP-9 (Yinlingquan) and CV-9 (Shuifen), supplemented by moxibustion at ST-36 and CV-6. Progressive clinical improvement was observed: by session 3, discharge volume significantly decreased; by session 5, pathological discharge ceased completely with clean undergarments; by session 6, all primary and secondary symptoms resolved entirely. Objective signs normalized progressively—tongue transformed from swollen with thick yellow greasy coating to pink with thin white coating, and pulse shifted from deep-weak-slow-slippery to normal rhythm. The participant also reported restored digestive function (formed stools, no postprandial bloating), elimination of cold sensation in extremities, improved sleep quality, and enhanced energy levels. Acupuncture effectively resolved fluor albus through dual mechanisms of Spleen Qi tonification and Dampness elimination, aligning with the TCM therapeutic principle "Jian Pi Chu Shi" (strengthening Spleen to resolve Dampness). This case demonstrates acupuncture's potential as a safe, non-pharmacological complementary therapy for gynecological disorders with metabolic-gastrointestinal etiology. Keywords: Fluor Albus, Acupuncture, Spleen Qi Deficiency, Dampness.  ABSTRAK Fluor albus merupakan keluhan ginekologi prevalensi di Indonesia dengan angka kejadian 27,60–90% pada wanita usia subur. Terapi konvensional berbasis anti mikroba sering menimbulkan efek samping dan resistensi obat, sehingga diperlukan alternatif terapi holistik berbasis Pengobatan Tradisional Tiongkok (TCM). Penelitian studi kasus ini bertujuan mengevaluasi manfaat asuhan akupunktur pada fluor albus dengan pola sindrom Defisiensi Qi Limpa disertai akumulasi Kelembapan. Partisipan adalah seorang wanita berusia 43 tahun dengan keluhan keputihan patologis berlebihan (sekret putih kekuningan, lengket, berbau), disertai kelelahan, kembung pasca-makan, feses tidak berbentuk, serta lidah gemuk dengan selaput kuning tebal berminyak dan nadi tenggelam-lemah-lambat-licin. Intervensi dilakukan sebanyak enam sesi akupunktur dua kali per pekan di Griya Sehat "de_maemun", Cirebonmenggunakan protokol titik SP-6, SP-4, ST-36, CV-6, GB-26, BL-20 (metode tonifikasi) dan SP-9, CV-9 (metode reduksi), dilengkapi moksibusi pada titik ST-36 dan CV-6. Evaluasi progresif menunjukkan regresi klinis bertahap: pada sesi ke-3 volume sekret berkurang signifikan; sesi ke-5 sekret patologis tidak lagi ditemukan pada pakaian dalam; sesi ke-6 seluruh gejala utama dan tambahan teratasi sempurna dengan normalisasi lidah (merah muda, selaput putih tipis) dan nadi (tidak tenggelam/lemah). Akupunktur efektif mengatasi fluor albus melalui mekanisme tonifikasi Qi Limpa dan eliminasi Kelembapan, sejalan dengan prinsip terapeutik TCM "Jian Pi Chu Shi" (memperkuat Limpa menghilangkan Kelembapan). Pendekatan diferensiasi sindrom berbasis etiologi metabolik-gastrointestinal terbukti memberikan respons klinis bermakna tanpa efek samping farmakologis. Kata Kunci: Asuhan Akupunktur, Fluor Albus, Keputihan Patologis, Defisiensi Qi Limpa.